The Relationship Between Social Interaction, Voice Behavior and Job Satisfaction - Sri Handayani; Dorothea Wahyu Ariani (JURNAL ILMU MANAJEMEN, 2026)
This study aimed to examine the effect of Leader-Member Exchange (LMX) and Team-Member Exchange (TMX) on employee voice behavior (EVB) and how EVB subsequently increases job satisfaction (JS). The study was conducted with 445 employees of a consulting service organization located in major cities in Indonesia. Validity testing was carried out using factor analysis, while reliability was assessed through internal consistency using Cronbach's Alpha to determine the questionnaire's suitability for the variables. Accordingly, correlation analysis was used to examine the relationships between variables, and structural equation modeling (SEM) with Smart-PLS was adopted to test the mediation model in accordance with theory and previous results. The results showed that TMX significantly increased EVB, whereas LMX did not. EVB was also observed to play a role in increasing JS. Furthermore, EVB effectively mediated the effect of TMX on JS but did not mediate the effect of LMX on JS. These results invariably strengthen the social exchange theory (SET) and the social penetration theory (SPT) that underpin the relationship models tested. Future research still needs to test the relationship model between the variables in this study to confirm the theory tested in the hypothesis.